2011
DOI: 10.1155/2011/843019
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity Caused by the Treatment with Platinum Analogues

Abstract: Platinum agents (cisplatin, carboplatin, and oxaliplatin) are a class of chemotherapy agents that have a broad spectrum of activity against several solid tumors. Toxicity to the peripheral nervous system is the major dose-limiting toxicity of at least some of the platinum drugs of clinical interest. Among the platinum compounds in clinical use, cisplatin is the most neurotoxic, inducing mainly sensory neuropathy of the upper and lower extremities. Carboplatin is generally considered to be less neurotoxic than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
106
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 53 publications
3
106
0
6
Order By: Relevance
“…It is well-known that cisplatin affects calcium homeostasis and its desired and undesired effects involve the change of calcium homeostasis (30). It has been reported that the clinical and side effects of cisplatin could be changed by altering the calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that cisplatin affects calcium homeostasis and its desired and undesired effects involve the change of calcium homeostasis (30). It has been reported that the clinical and side effects of cisplatin could be changed by altering the calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of oxidative stress and release of NO are considered to be the prime factors for cisplatin-induced nephrotoxicity (Pan et al 2009). Superoxide (Davis et al 2001), hydrogen peroxide (Kadikoylu et al 2004) and hydroxyl (Shino et al 2003) radicals increased by cisplatin, stimulates lipid peroxidation (Sadzuka et al 1992) and results in the inhibition of antioxidant enzyme activities (Mora et al 2003), which is responsible for nephrotoxicity (Amptoulach & Tsavaris 2011;Naqshbandi et al 2012;Ognjanovic et al 2012). To ameliorate these side effects, complementary agents of high antioxidant potential have been recently investigated (Monti & Yang 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity to the peripheral nervous system is one of the key dose-limiting toxicities. 10 All three drugs also have relatively short blood circulation times, resulting in suboptimal pharmacokinetics. For cisplatin, nephrotoxicity as well as nausea and vomiting have significantly limited its clinical use.…”
Section: Introductionmentioning
confidence: 99%